Premalignant features of the prostate can be ameliorated by Uvaria chamae root extract: Modeling prostate cancer with cadmium and alternative treatment option in adult Wistar rats - Edem GD; Sakpa CL; Ezeuko VC (Ibom Medical Journal)
Background: Prostate cancer is the most commonly diagnosed cancer and the leading cause of cancer deaths in males worldwide. Mortality attributed with prostate cancer is strongly associated with the age of an individual with relatively higher incidence noticed among aged males.